Teacher's Pedagogical Content Knowledge (PCK) in implementing Realistic Mathematics Education (RME) - Tuti Zubaidah; Rahmah Johar; Dewi Annisa; Yulinar Safitri (Beta: Jurnal Tadris Matematika, 2023)
[English]: Pedagogical Content Knowledge (PCK) is crucial for mathematics teachers in teaching and learning due to the fact that mathematics is an abstract and interrelated subject; requiring adequate knowledge on the content and instructional practices. Applying Realistic Mathematics Education (RME) help students learn in meaningful way since it starts with contextual problems. Therefore, to realize the meaningful learning, teachers need to have PCK in implementing RME. This study aims to analyze two teachers' PCK in implementing RME for geometry topic. Prior to the classroom teaching, both teachers received teacher professional development program regarding RME. Data in this study were collected through classroom observation and interviews which were the analyzed qualitatively. The results of the analysis show that both teachers have similar PCK in applying RME. The PCK indicator fulfilled by the teachers is further discussed in this paper. [Bahasa]: Pedagogical Content Knowledge (PCK) atau pengetahuan pedadogis dan konten sangat diperlukan bagi guru matematika dalam pembelajaran karena matematika bersifat abstrak dan saling berkaitan, sehingga memerlukan penguasaan materi dan perencanaan pembelajaran yang baik. Pembelajaran dengan Pendidikan Matematika Realistik (RME) membantu siswa belajar bermakna karena dimulai dari masalah nyata yang terdapat dalam kehidupan sehari-hari atau konteks. Oleh karena itu, untuk mewujudkan pembelajaran bermakna tersebut, guru harus memiliki PCK dalam menerapkan RME. Penelitian ini bertujuan menganalisis PCK dua orang guru dalam menerapkan RME pada materi geometri. Kedua guru tersebut telah mengikuti program pengembangan profesional guru sebelum pembelajaran dilaksanakan. Data dalam penelitian ini dikumpulkan melalui observasi dan wawancara yang dianalisis secara kualitatif. Hasil penelitian menunjukkan bahwa kedua guru memiliki PCK yang sama dalam menerapkan RME. Indikator yang dipenuhi dibahas lebih lanjut dalam tulisan ini.